Peter Handke Narrative Worlds - Pictorial Orders - Renner, Rolf G. (Stuttgart : J.B. Metzler : Imprint: Palgrave Macmillan, 2023)
The volume presents Handke's works from Hornissen (1966) to Das zweite Schwert (2020) in individual analyses and at the same time opens up overarching orientations of Handke's writing. The autoreflexive traces that characterise the author's experimental early work are perpetuated in a middle phase by a return to traditional forms of epic narrative and literary models that is philosophically influenced. In the late work, these approaches give rise to a comprehensive poetology of narrative that links all the texts together. In the process, previously developed motifs are condensed into overarching thematic complexes. Alongside the reality of war, the relationship between image and writing, text and film, social and media developments of modernity come to the fore. The reference of Handke's texts to images of the painterly tradition and visual strategies of his writing are given special weight. This book is a translation of the original German 1st edition Peter Handke by Rolf G. Renner, published by Springer-Verlag GmbH Germany, part of Springer Nature in 2020. The translation was done with the help of artificial intelligence (machine translation by the service DeepL.com). The author has subsequently revised the text further in an endeavour to refine the work stylistically. Springer Nature works continuously to further the development of tools for the production of books and on the related technologies to support the authors.
1. Narrative worlds/image orders. An introduction to the text -- 2. Literary self-assertion and experimentation with form: The narrative beginnings -- 3. Experimentation and design: The plays, prose works and radio plays up to 1973 -- 4. Rediscovery of subjectivity: Lines of development in poetry -- 5. Return to narrative and new subjectivity -- 6. Return to the beginnings of the ego and the promise of images -- 7. Re-establishment of the narrator in the return to tradition -- 8. Self-reflection and poetological sketches: The journals, sketches and notes -- 9. Transmutation of the self in writing -- 10. The experiment of remembering description -- 11. The fundamental other of poetry: Handke's double discourse on Serbia -- 12. Between drama and epic: The plays after 1989 -- 13. The competition between word and image -- 14. Dialectic of history and revocation of modernity -- 15. Basic lines of Handke's reception in literary criticism and science -- Bibliography.
Keywords: Literature, Modern -- 20th century; Literature, Modern -- 21st century; Contemporary Literature